Beam Search Approach for the Multiobjective Flow-shop Scheduling Problem - Kanesan , Muthusamy; Ishii, Hiroaki; Mohri, Shintaro; Masuda, Teruo (2000)
In this paper, we address the problem of minimizing maximum completion time and average flow-time simultaneously in a flow-shop environment. We formulate the problem as a bi-criteria flow-shop scheduling problem in which it minimizes the maximum completion time and average flow-time. We develop and propose an approximation algorithm to find the non-dominated solutions for the above problem. As a solution technique, we propose a new approach based on the beam search with gap concept. (Abstract by authors)